Coryphoid Palm Fruits and Seeds from The Danian of Nûgssuaq, West Greenland. - Koch, B. Eske (Meddelelser om Grønland, 1972)
Two species of coryphoid palm fruits are described, Coryphoides poulseni n. gen. et n.sp. and Coryphoicarpus globoides n.gen. et n.sp. The former has been found in the Upper Danian (formerly Lower Paleocene) or Qaersutjægerdal in central Nugssuaq, the latter in the Lower Danian of the valley of Tunorssuaq, Nûgssuaq. The chief criteria for the determination of these fossil species as coryphoid palms are: 1) the big bulbous ingrowth from the functional pericarp of the placental region into the seed along the axis of the fruit (here called the columella), 2) the seed consisting mainly of a large cup-shaped endosperm , surrounding the columella, and 3) the small, saccate embryo inserted from the surface of the seed into the endosperm. Coryphoidcs poulseni n. gen. et n. sp. is distinguished by the position of the embryo, the existence of a ’chalaza valve’ and the characteristics or the columella, including the shape of the placental scar. Coryphoicarpus globiodes n. gen. et n.sp. shows the same basic structure as Coryphoides poulseni n. gen. et n. sp., but differs from the latter in size and shapeof the placental scar, shape of columella, course or the funiculus, position of chalaza, shape of ’the chalaza valve’ and the position of the embryo. The determinations are based upon a comparative study of a number of recent coryphoid palms and or Palmospermum excavatum REID & CHANDLER,